Cerium Oxide Nanoparticles Biosynthesized Using Fresh Green Walnut Shell in Microwave Environment and their Anticancer Effect on Breast Cancer Cells. Issue 8 (12th July 2022) - Sulak, Mine; Turgut, Gurbet Celik; Sen, Alaattin
Abstract: In this study, cerium oxide nanoparticles (CONPs) were synthesized using fresh green walnut shell extract in microwave environment. The morphology and structure of the CONPs were determined using ultraviolet‐visible (UV/VIS), attenuated total reflection‐Fourier transform infrared (ATR‐FT‐IR), X‐ray diffraction (XRD), energy‐dispersive X‐ray (EDX) spectroscopy, and scanning electron microscopy (SEM). Crystal purple staining, Annexin V‐FITC detection, RT‐PCR, P53, and NF‐κB luciferase reporter assays were performed to evaluate the mechanism of action of CONPs in breast cancer cell lines (MCF7). The biosynthesized CONPs showed cytotoxic effects and induced apoptosis in MCF7 cells. Furthermore, CONPs induced P53 expression and suppressed NF‐κB gene expression, both of which were confirmed using reporter assays. Based on the present results, it was concluded that CONPs can induce apoptosis by acting on P53 at the transcriptional level and may cause cell death by suppressing NF‐κB‐mediated transcription. Abstract :